AJARAN BHATARA SIWA DALAM LONTAR ANDHA BHUWANA KAJIAN PENDIDIKAN KARAKTER - I Wayan Artayasa (Guna Widya: Jurnal Pendidikan Hindu, 2021)
Bhatara Shiva's teachings comprise various moral, ethical, and susila values. This value is exceptionally well practised and implemented in daily life. This value is included in Balinese Hindu religious texts, notably lontar texts. From ancient times to the present, the existence of lontar manuscripts to be studied and researched proceeds to expand to reveal character education values. One of the teachings of Hinduism is conveyed through stories. Character education is conveyed so that humankind is presented descriptions of knowledge, between good and bad; thus, they can choose one of those options. Both good and bad deeds have their respective consequences, which of course all religions expect that humans frequently do good things. Lontar Andha Bhuwana carries out stories regarding the teachings of Bhatara Shiva which need to be observed because they contain conversations between parents as a father (Bhatara Siwa), as a mother (Bhatara Giri Putri), and as a child (Bhatara Gana / Ganesha). This story is highly relevant as a reflection of education, primarily character education and has meaning in forming household harmony. Obligations as children devoted to their parents, be grateful for life, self-purification (pangruatan), and harmonise nature.